Bridging Transcultural Divides: Asian Languages and Cultures in Global Higher Education - Xianlin, Song; Kate, Cadman (University of Adelaide Press, 2012)
This volume presents the diverse approaches and achievements of scholars of Asian cultures and languages in today's global academy. Recent vast increases in student numbers and ethnic diversity have created pressing challenges for a higher education which engages with contemporary concerns for Asian societies as well as for Asian students involved in Western education. This collection of scholarly analyses demonstrates the centrality and significance of Asian Studies and languages for these globalising academic communities. Significantly, it demands a rethinking of traditional 'intercultural' education. In so doing, it brings empirical knowledge as well as multicultural interpretation and multilingual expertise to throw new light on the challenges in higher education today, and to open up new understandings of the demands of the future. - Professor John Makeham Head, Department of Chinese Studies, The Australian National University